Recent advances in the preparation of zeolites for the selective catalytic reduction of NOx in diesel engines. Issue 6 (6th December 2018) - Zhang, Ling; Wu, Qinming; Meng, Xiangju; Müller, Ulrich; Feyen, Mathias; Dai, Daniel; Maurer, Stefan; McGuire, Robert; Moini, Ahmad; Parvulescu, Andrei-Nicolae; Zhang, Weiping; Shi, Chuan; et al.
Abstract : Metal-exchanged zeolites with small pore sizes have attracted much attention in recent years due to their application in the selective catalytic reduction (SCR) of NOx in diesel engines. Abstract : Metal-exchanged zeolites with small pore sizes have attracted much attention in recent years due to their application in the selective catalytic reduction (SCR) of NOx in diesel engines. Typically, copper-chabazite ( e.g. Cu-SSZ-13) has been gradually used as an SCR catalyst in heavy-duty diesel vehicles over the last decade due to its relatively excellent catalytic performance and stability. However, most SSZ-13 zeolites are still prepared via the traditional hydrothermal process in the presence of organic templates, requiring consecutive solid separation and thermal treatment steps to achieve the final zeolite products. In recent years, several strategies for the environmentally friendly preparation of zeolites have been reported, which are also applicable for the synthesis of zeolites for emission control applications. These concepts include copper–amine templating, organotemplate-free synthesis, and solvent-free synthesis. In this review, we briefly summarize the potential advantages of the environmentally friendly synthesis of zeolites for SCR.